The efficiency of the Swedish trappy in catching freshwater crayfish Pacifastacus leniusculus and Astacus leptodactylus - Harlio?lu, Muzaffer Mustafa (My University, 1999)
The efficiency of the Swedish trappy in catching Pacifastacus leniusculus and Astacus leptodactylus was studied. The results showed that the Swedish trappy was very effective at catching both P. leniusculus and A. leptodactylus. In the concrete tank study, 71.6% of the total crayfish in the A. leptodactylus tanks and 60% of the total crayfish in the P. leniusculus tanks had been caught with baited traps at the end of the experiment. On the other hand, it was found that there was considerable movement of crayfish in and out of the traps, and consequently a decline in the number of crayfish in some traps over time. The results also showed that there was no significant difference in the total number of captured P. leniusculus and A. leptodactylus (P>0.05), but a significantly greater amount P. leniusculus escaped from the trap and changed traps than of A. leptodactylus (P<0.001). It was also observed that baited traps caught significantly more crayfish of both species than unbaited traps (P<0.05). The present study reveals that in order to maximise catching efficiency it is better to empty the traps a number of times during the night. In addition, because the escape rate of P. leniusculus is significantly higher, the opening of the entrances of the Swedish trappy should be reduced for this species.
Keywords: Astacus leptodactylus; Crayfish; Pacifastacus leniusculus; Swedish trappy; Trapping